Running Your Programs - Halpin, Terry; Rugaber, Spencer (Taylor & Francis Group, 2015)
LogiQL programs and the workspaces they deal with are managed by a command interpreter invoked by issuing the lb command to the operating system’s shell. At a high level, these commands interact with a server process responsible for managing one or more workspaces. This includes creating them, adding and removing blocks, installing data, and displaying results.